Using Interactive Methods in Teaching English to Students in Higher Educations - Gulamkadirovna, Karimova Zulnura (European Journal of Life Safety and Stability (2660-9630), 2023)
Nowadays, when the demand for learning foreign languages is increasing, different methods of language teaching and learning are developing day by day. In this regard, interactive methods give the expected results. Interactive methods are student-oriented methods that activate students and encourage independent thinking. This article presents ideas about learning English using interactive methods in higher education institutions.